Globalisasi dan Rezim Demokrasi Poliarki: Kebijakan Integrasi Ekonomi Indonesia - Winarno, Budi (Universitas Muhammadiyah Yogyakarta, 2014)
Globalization on the one hand has reduced significantly the traditional roles of the state in the international level, while on the other hand it strengthened the positions of new transnational actors such as international organization, MNC, and society. At the domestic level, in many democratic nations, it changed the quality of democracy in which policies are no longer based on the interests of the people but to protect the penetration of global corporations. This article tries to explain, particularly in the case of Indonesia, how those decisions do not accommodate people as majority but only serve the interests of both local ruling elite and the transnational bourgeois. Democracy which ideally should be able to ensure the participation of the people in the decision making process apparently has been manipulated by a group of minority elites.